2014
DOI: 10.4161/auto.28768
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of MAPK/JNK-MTORC1 signaling leads to premature loss of organelles and nuclei by autophagy during terminal differentiation of lens fiber cells

Abstract: Although autophagic pathways are essential to developmental processes, many questions still remain regarding the initiation signals that regulate autophagy in the context of differentiation. To address these questions we studied the ocular lens, as the programmed elimination of nuclei and organelles occurs in a precisely regulated spatiotemporal manner to form the organelle-free zone (OFZ), a characteristic essential for vision acuity. Here, we report our discovery that inactivation of MAPK/JNK induces autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 92 publications
6
99
2
Order By: Relevance
“…Indeed, previous studies have demonstrated that MAPK8/9 can be activated in response to TORC1 signaling [35] and that TORC1 activation can require MAPK8/9 signaling [28]. However, we found no requirement for MAPK8/9 upstream (Figure 1) or downstream (Figure 2) of TORC1 during starvation-induced autophagy.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Indeed, previous studies have demonstrated that MAPK8/9 can be activated in response to TORC1 signaling [35] and that TORC1 activation can require MAPK8/9 signaling [28]. However, we found no requirement for MAPK8/9 upstream (Figure 1) or downstream (Figure 2) of TORC1 during starvation-induced autophagy.…”
Section: Discussioncontrasting
confidence: 51%
“…The requirement of MAPK8 for starvation-induced autophagy [5] may therefore reflect a role for MAPK8 upstream or down-stream of MTOR. Indeed, previous studies have demonstrated that MAPK8/9 can be activated in response to TORC1 signaling [35] and that TORC1 activation can require MAPK8/9 signaling [28]. Alternatively, MAPK8/9 and TORC1 may function in parallel pathways that control autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In lens development, deficiency of Atg5 or phosphatidylinositol 3-kinase catalytic subunit type (Pik3c3) failed to abolish organelle-free zone (ONF) formation required for lens transparency (50). But more recent data indicate that the mammalian target of rapamycin complex 1 (mTOR-1) signaling is required for proper development of the OFZ in lens (51). These contrasting observations could be explained by differences in gene targeting approaches (choice of exon deletion), cell type (context) dependence, influence of genetic background, and timing of examinations .…”
Section: Discussionmentioning
confidence: 99%
“…Lens organelle degradation has recently been linked to autophagy-related processes (Basu et al, 2014) and mitophagy (Costello et al, 2013). We first examined the degradation of mitochondria (visualized by Tomm20 antibodies) and of ER (visualized by PDI antibodies) in control and Snf2h-depleted lenses.…”
Section: Lenses P27mentioning
confidence: 99%